Implementation of Regulations and Policies for Nursing Care Quality in Hospitals Worldwide - Edy Wuryanto (Persatuan Perawat Nasional Indonesia Jawa Tengah, 2024)
This systematic review examines the global implementation of regulations and policies aimed at enhancing the quality of nursing care in hospital settings. Through a comprehensive literature search, 20 studies were identified and analyzed. The review focuses on various regulatory frameworks, accreditation standards, and governmental policies that influence nursing care quality. The findings reveal that while regulations generally improve patient outcomes and care standards, challenges such as resource limitations, enforcement variability, and cultural resistance persist. The review concludes with recommendations for future research and policy development to address these challenges and improve nursing care quality globally.